On Psilorhynchus sucatio and P. nudithoracicus, with the description of a new species of Psilorhynchus from northeastern India (Ostariophysi: Psilorhynchidae) - Conway, Kevin W.; Dittmer, Drew E.; Jezisek, Laci E.; Ng, Heok Hee (Zootaxa, 2013)
Psilorhynchus sucatio (Hamilton) is redescribed based on the examination of 462 specimens, 13–67 mm standard length (SL). Psilorhynchus nudithoracicus Tilak & Husain is redescribed based on the examination of 97 specimens, 10–68 mm SL. Psilorhynchus gracilis Rainboth is placed in the synonymy of P. nudithoracicus. Psilorhynchus hamiltoni, a new species and a member of the P. balitora species group, is described from the Tista River in West Bengal, India. It is distinguished from all other members of the P. balitora species group by having a well-developed lateral stripe, 6–7 poorly developed saddles that do not make contact with the lateral blotches, 7–11 lateral blotches, 34–35 lateral line scales, 9+8–9 principal caudal-fin rays, 36 total vertebrae, and the ventral surface between paired fins with a broad rectangular scaleless patch. A key to the species groups of Psilorhynchus is also provided, as are revised diagnoses for the P. balitora and P. nudithoracicus species groups.